2021
DOI: 10.47162/rjme.61.4.26
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological and immunohistochemical aspects of bone tissue in aseptic necrosis of the femoral head

Abstract: Femoral head osteonecrosis, also known as avascular necrosis, is a disease with a multifactorial etiology, characterized by a profound change of bone architecture, which leads to the diminishing of bone resistance and femoral head collapse. The main causes that lead to femoral head necrosis are represented by the decrease of local blood perfusion and increase of intraosseous pressure, because of an excessive development of adipose tissue in the areolas of the trabecular bone tissue in the femoral head. The his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Over time, this can result in the loss of articular cartilage, exposing the underlying bone and leading to the formation of osteochondral lesions. It is important to note that AVN and its association with chondral and osteochondral lesions can vary depending on the specific location and extent of the AVN, as well as individual patient factors [ 28 30 ].…”
Section: Etiologymentioning
confidence: 99%
“…Over time, this can result in the loss of articular cartilage, exposing the underlying bone and leading to the formation of osteochondral lesions. It is important to note that AVN and its association with chondral and osteochondral lesions can vary depending on the specific location and extent of the AVN, as well as individual patient factors [ 28 30 ].…”
Section: Etiologymentioning
confidence: 99%
“…Interestingly, some studies have reported a local decrease in B‐cell counts in osteonecrosis, while high numbers of activated B cells are presented in the blood 228,232,239,240 …”
Section: Implant‐related Factors Altering Bone Metabolismmentioning
confidence: 99%
“…Compared to healthy people, ONFH patients show significantly higher numbers of CD5+CD19+ B1 cells, CD86+CD19+ and CD95+CD19+ activated B cells, and CD27+CD95+CD19+ memory B cells in the blood ( 79 , 85 ). Conversely, osteonecrotic tissue shows local decreases in the number of memory B cells and the total number of B cells ( 86 ). These observations emphasize the importance of B cells in maintaining the normal bone microenvironment and the ability of different B cell subtypes to influence the progression of osteonecrosis.…”
Section: Immune Cells and Osteonecrosismentioning
confidence: 99%